2019
DOI: 10.3892/mmr.2019.10027
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the ERK/Creb/Bcl‑2 pathway protects periodontal ligament stem cells against hydrogen peroxide‑induced oxidative stress

Abstract: Periodontal ligament stem cells (PDLSCs) are promising stem cells sources for regenerative medicine, particularly clinical periodontal ligament repair. It is critical to maintain high quality and a large quantity of PDLSCs for clinical usage. However, how PDLSCs respond to environmental stimuli, including reactive oxygen species (ROS), is poorly understood. The aim of the present study was to investigate how PDLSCs react to oxidative stress and the underlying mechanisms. Hydrogen peroxide-induced oxidative str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 60 publications
4
14
1
2
Order By: Relevance
“…PDLSCs were treated with H 2 O 2 (100 μmol/L) to induce oxidative stress. Previous research has confirmed that H 2 O 2 (100–500 μmol/L) is cytotoxic and promotes cell apoptosis in PDLSCs 26 . The present study further showed that H 2 O 2 treatment decreased klotho and UCP2 levels.…”
Section: Discussionsupporting
confidence: 86%
“…PDLSCs were treated with H 2 O 2 (100 μmol/L) to induce oxidative stress. Previous research has confirmed that H 2 O 2 (100–500 μmol/L) is cytotoxic and promotes cell apoptosis in PDLSCs 26 . The present study further showed that H 2 O 2 treatment decreased klotho and UCP2 levels.…”
Section: Discussionsupporting
confidence: 86%
“…Notably, the levels of anti-apoptotic and pro-apoptotic proteins in the Bcl-2 family were directly regulated by ERK signaling through their transcriptional and posttranslational mechanisms. Bcl-2 transcription mediated by the Creb pathway is driven by ERK activation [38,39], and Bcl-2 is phosphorylated stably by ERK [40]. An ERK inhibitor was shown to induce apoptosis by increasing Bax levels and abolishing Bcl-2 levels [41], a result consistent with our finding that ERK inhibition by U0126 enhances apoptotic induction by ETD and enhances the ratio of Bax/Bcl-2.…”
Section: Discussionsupporting
confidence: 89%
“…However, we observed a proportional reduction in both total and phosphorylated CREB by ErbB TKIs and the ERK inhibitor SCH772984, implicating that with chronic ErbB TKI treatment, the role of phosphorylated ERK involves maintaining CREB expression and phosphorylation, and this occurs at a post-translational level, given the unchanged CREB mRNA level, although the mechanism has not been determined. Notably, other publications did not observe a similar effect of ERK inhibitors on CREB expression (Fu et al, 2019;Li et al, 2018), a discrepancy which might be explained by the shorter period (maximum 24 hours) of exposure in those studies as compared to ours (6 days).…”
Section: Discussioncontrasting
confidence: 85%